THE FEASIBILITY OF EXPORTING GEOGRAPHICALINFORMATION SYSTEM DATA TO GOOGLE EARTH - Ali, Sabah; Ali, Ali (Iraqi Journal of Science, 2024)
Image satellite is one of the important sources for the Geographical InformationSystem (GIS). With world-level coverage of satellite, aerial photography, streetspoints of interest and more, made the Google Earth (GE) as one of the geobrowsersprograms that enable data with a spatial component to be used by both GIS and non-GIS usersThe objective of the present study is to explore the feasibility to export and integrateexisting GIS format data including shapefiles into a GE format for display as a layerat the same location of the study area, and manipulation by using various ArcGIS9.2tools. Export_to_KML software was used for converting the data from GIS formatto GE format. This process is potentially very useful in the direct interaction of theGIS datasets over the internet by desktop mapping tools such as GE , where theirintegration with GIS information is especially helpful in the viewing theinformation in a spatial context. All the created shapefiles of this study have beendone by author using ESRI's ArcGIS9.2 Desktop and defined according toWGS84_UTM_Zone 38N projected system.The results revealed that both GIS vector and attribute data can be effectivelyexported and visualized using GE. Moreover, most of the GE functions can beapplied on the exported GIS layers that can be visualized on the GE window.